The Link Between Paraphilic Disorder and Sexual Crime - N. K., Tharshini; Fauziah, Ibrahim (Human Resource Management Academic Research Society (HRMARS), 2023)
A substantial body of literature corroborates that paraphilic disorder is a risk factor for sexual crime, making it an important area of scientific investigation. The DSM-5 refined the term paraphilic as referring to strange, persistent, and intense atypical sexual interest other than genital stimulation alone. The present review using the Preferred Reporting Items for Sistematic Reviews and Meta-Analyses (PRISMA) guidelines summarised the link between paraphilic disorder and sexual crime. Keywords such as “paraphilic behaviour”, “sexual crime”, “sex aggression”, and “paraphilic interests” were typed into the Taylor & Francis Online, Wiley Online Library, PubMed, and SAGE databases. Articles listed under the indexing of Scopus and ISI Web of Science were used as a source of guidelines to find information related to the link between paraphilic disorder and sexual crime. The result indicates that obsession with sex has been found to be one of the strongest predictors of recidivism among men diagnosed with paraphilic disorder and medication can play a significant role in controlling hypersexual behaviour, preoccupation, and sexual compulsion. In summary, this review is expected to provide a more refined and informed understanding of sexual offending behavior, with important implications for future research, assessment, and treatment issues.